Sovereign risk premia: The link between fiscal rules and stability culture - Steffen Osterloh; Friedrich Heinemann; Alexander Kalb (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
There is a growing empirical literature studying whether fiscal rules reduce borrowing costs. Nevertheless, it remains an open question whether these rules are effective genuinely or just because they mirror fiscal preferences of politicians and voters. In our analysis of European bond spreads, we shed light on this issue by employing several types of stability preference related proxies. These proxies refer to a country's past stability performance, government characteristics and survey results related to general trust. We find evidence that these preference indicators have an influence on risk premia and dampen the measurable impact of fiscal rules. Yet, the interaction of stability preferences and rules points to a particular potential of fiscal rules in countries with a historically low stability culture.
Keywords: H63; H87; G12; 330